Discovery Learning,Teks Laporan APPLICATION OF DISCOVERY LEARNING MODEL IN INTERPRETING TEXT ORAL RESULTS OF OBSERVATION RESULTS IN CLASS X STUDENTS IPA.2 STATE 1ST HIGH SCHOOL - Rita Arianti; Asih Ria Ningsih (JURNAL PENDIDIKAN ROKANIA, 2019)
This research is motivated by the low skill of interpreting the text of the report on the results of student observations verbally. The type of this research is Classroom Action Research. The method of this research is qualitative and quantitative methods. The purpose of this study is to improve the process and results of learning to interpret the text of the report on student observation verbally through the application of the Discovery Learning model. The results of these studies are (1) The quality of student activities shows that the poor category is in the first cycle, which is 7.35%, cycle II is 3.23%, cycle III is 1.48%. The quality of student activities in the fairly good category is the first cycle, which is 72.35%, cycle II is 48 52%, cycle III is 36, 76%, cycle IV becomes 7.35%. The quality of student activities in the good category is cycle I which is 20.30%, cycle II is 45.29%, cycle III is 50%, and Cycle IV is 32, 06%. While the quality of student activities in the excellent category is nonexistent, Cycle II increases to 2.94%, cycle III increases to 11.76%, cycle IV increases again to 60.58%. (2) Increasing the completeness of prasiklus learning outcomes by 38.23% with a class average of 66.85 to 50% in the first cycle with a class average of 73.48, increasing again in the second cycle to 70.58% with a class average of 76.66, increasing again in the third cycle to 82.35% with a class average of 79.40, increasing again in the IV cycle to 97.05% with a class average of 84.50. Based on the results of these studies can be concluded that the application of the Discovery Learning model is able to improve the activity and learning outcomes of class X IPA.2 students of SMA Negeri 1 Rambah in interpreting the text of reports on observations orally.